Neuroimaging somatosensory perception and masking. (8th January 2017) - Meador, Kimford J.; Revill, Kathleen Pirog; Epstein, Charles M.; Sathian, K.; Loring, David W.; Rorden, Chris
Abstract: The specific cortical and subcortical regions involved in conscious perception and masking are uncertain. This study sought to identify brain areas involved in conscious perception of somatosensory stimuli during a masking task using functional magnetic resonance (fMRI) to contrast perceived vs. non-perceived targets. Electrical trains were delivered to the right index finger for targets and to the left index finger for masks. Target intensities were adjusted to compensate for threshold drift. Sham target trials were given in 10% of the trials, and target stimuli without masks were delivered in one of the five runs (68 trials/run). When healthy dextral adult volunteers (n=15) perceived right hand targets, greater left- than right-cerebral activations were seen with similar patterns across the parietal cortex, thalamus, insula, claustrum, and midbrain. When targets were not perceived, left/right cerebral activations were similar overall. Directly comparing perceived vs. non-perceived stimuli with similar intensities in the masking task revealed predominate activations contralateral to masks. In contrast, activations were greater contralateral to perceived targets if no masks were given or if masks were given but target stimulus intensities were greater for perceived than non-perceived targets. The novel aspects of this study include: 1) imaging of cortical and subcortical activations in healthy humans related to somatosensory perception during a masking task, 2) activations in the human thalamus and midbrain related to perception of stimuli compared to matched non-perceived stimuli, and 3) similar left/right cerebral activation patterns across cortical, thalamic and midbrain structures suggesting interactions across all three levels during conscious perception in humans. Highlights: fMRI study of conscious perception of somatosensory stimuli during a masking task. Activations in the human thalamus and midbrain related to perception. Similar left/right activation patterns across cortex, thalamus and midbrain. Patterns suggest interactions across all three levels during conscious perception.